RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBERIAN KOMPOS LIMBAH KAKAO PADA TANAH INSEPTISOL - Dyanne Gisella P. Tambak; Luthfi Aziz Mahmud Siregar; Rosmayati Rosmayati (Jurnal Agroekoteknologi, 2013)
ABSTRACTGrowth and Yield Responses of some Onion Varieties (Allium ascalonicum L.) with Cocoa WasteCompost on The Inceptisol supervised by Luthfi Aziz Mahmud Siregar and Rosmayati. The studyaimed to know respons of four onion extent on the provision of cocoa waste compost on inceptisol,Research was conducted at campus area Tengku Amir Hamzah University, Pancing. Medan Estate,Deli Serdang (±15 m above sea level) from April -Juli 2012. This study used a randomized blockdesign the frist factors was the variety such as Medan Variety, Maja Variety, Kuning Variety andBali Karet Variety. The second factor was with 4 levels of cocoa waste compost, namely 0 g, 236 g,472 g, and708 g. The data obtained were analyzed using analysis of variance, followed by HonestlySignificant Difference test. The results showed that the varieties significantly of plant height,number of leaves at 2 week after plant,bulbs per sample,fresh weight per sample, dry weight persample, fresh weight per plot, dry weight per plot and harves time.Respons of giving cocoa wastecompost not significantly to all observation parameters. Interaction between varieties and dosescocoa waste compost ot significantlyto all observation parameters.Keywords: onion,cocoa waste compost, varieties, inceptisol soil.